Risk management in IT projects: Case study - Artur Biskupek (Trends Economics and Management, 2018)
Purpose of the article: The first part of the article shows summarised information on risk management in projects based on the literature review. The second part of the article is a case study made on the basis of materials made available by the company implementing the AZTiE project. The case study shows how the risk management was carried out in the project. The techniques and methods of risk management used by the project manager were presented and risk groups were provided with assigned example risk factors, as well as the risk control plan envisaged for the specific factor. Methodology/methods: This article consists of two parts. The first part was developed on the basis of a literature study on project management and risk management in projects, in particular in IT projects. The second part was prepared on the basis of the consent of the AIUT Company and documents provided by the company. The documentation related to project management was analysed against this article. In particular, the basis for the study were documents such as progress reports, internal progress report, a static risk assessment card, Maximo training documentation, a risk management plan and identified risk factors along with control plans. Scientific aim: The aim is to present the course of the risk management process in a real IT project. Findings: The conclusion that can be drawn after the case study is that active and structured risk management in the project is one of the key success factors in the project. Conclusions: It is important that the entire risk management process is standardizsed and managed in an active manner. In the case study below, risk management was one of the success factors of the entire project.
Keywords: M15; M19; 650; project management; risk management; case study; IT project; risk factors; risk process